Performance and cost-benefit analysis data for three hatcheries operating as businesses in Timor-Leste. - Pant, Jharendu; Teoh, Shwu Jiau; Bhujel, Ram C.; Du Carmu, Adriano; De Jesus, Lucas Soares (2024)
These datasets include (a) hatchery performance data, such as egg production, fry survival rates, and monosex fry output, and (b) economic data on hatchery investments and operational costs, including capital expenditures, feed costs, and labor costs, as well as revenue from broodfish and monosex fry sales.